An Investigation into the Gender-Based Ability of Secondary School Students to Learn English as a Foreign Language Concerning Biases and Gender in Language Learning - Isbahi, Muhammad Baiqun (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
The language learning process promotes inclusivity by accounting for differences in intelligence regarding English as a foreign language between male and female pupils, which has a direct impact on their proficiency in language acquisition. The present study examines the gender-based disparity in language acquisition, concentrating on the English language competence of secondary school pupils. By examining the correlation between gender identity and English learning outcomes, this study seeks to fill a knowledge deficit regarding the inclusiveness of the language learning process. The researchers apply feminist stylistics and systemic functional linguistics to the analysis of written text products of high school pupils, which were gathered as part of an extensive data collection effort. Utilizing this analysis, they investigate how texts are constructed and scrutinize the impact of gender on the selection of linguistic structures. The results obtained from this research enhance our comprehension of disparities in language acquisition based on gender and provide valuable perspectives for the enhancement of language education methodologies that promote fairness and inclusivity for every student.